Biological evaluation of animal and vegetable protein test feeds in broilers and rats - Khalique, A.; Marghazani, I. B. (Revista Veterinaria, 2012)
Study was conducted to know the biological value of fish meal, meat meal, blood meal, sesame oil meal, cottonseed meal, and guar meal (Cyamopsis tetragonoloba) in two different species (ten day old broiler chicks, n=96; and weaning albino rats, n=64). These protein sources were added into nitrogen free diet on protein equivalent basis to formulate eight different diets including six test diets, a basal and a standard diet. Results revealed that both chicks and rats showed significant differences (p<0.05) in feed intake, weight gain and feed conversion ratio for animal and protein feeds. Fish meal in most of the measurements was similar (p>0.05) to casein in chicks. Weight gain ranked in declining order for diets containing fish meal, meat meal, sesame oil meal, cotton seed meal, blood meal and guar meal in both species. On standard stock diet ad libitum after drastic restriction period, both species showed a compensatory growth and nitrogen retention.